The Implementation of Using Role playing Method to Improve Cognitive Aktivities and Learning Outcomes Students' on Excretion System Material in SMPN 1 Batang - Adiba, Daniar Arof; Endang Susilowati, Sri Mulyani; Yuniastuti, Ari (FMIPA UNNES, 2018)
One of the main learning problems in school today is the low absorptive capacity of students as evidenced by the average of the student’s learning outcomes is always still under KKM. The reason is that the learning conditions are still conventional and is still teacher centered learning so it does not touch the dimensional realm of the students themselves. The learning method implemented by the teacher is more dominated by teachers, so students tend to be passive and not given access to develop independently. This illustrates that the process of learning that takes place is not optimal. Efforts to achieve a high absorption students is realized by applying an active learning and fun. Appropriate learning method is a method of role playing. Learning to use the method of role playing is learning that requires students to actively participate in the learning and mastery learning materials development of imagination. The purpose of this study to apply the method of role playing in  order to enhance the activity and the cognitive achievement of students on the material excretory system in SMPN 1 Batang. The study population was half of second class VIII SMP N 1 Batang and sample used is class VIII A and VIII E. Design study used is a quasi-experimental design from of pretest-posttest control group design. The results showed that the implementation of the method of role playing on learning excretory system can increase the activity and cognitive learning outcomes. The result of the increase was gotten in using N-Gain. Results obtained from the data that there is signifiant difference between the results before and after treatment (pretest-posttest). Based on the test results of N-gain, increased cognitive achievement experimental class (VIII A) amounted to 0.633 (moderate) and grade control (VIII E) 0.32 (moderate). Based on t test, showed that the value probability (sig.) <0.05 then Ho is rejected and Ha accepted. It means that there are differences in cognitive learning outcomes significantly between the control and the experimental class. The activity of students in class VIII A of 82.27% (very active) and VIII E amounted to 75.50% (Active). This indicates that the use of role playing method can increase the activity and cognitive learning outcomes of students.